2020
DOI: 10.1101/2020.08.01.232249
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dense poly(ethylene glycol) coatings maximize nanoparticle transport across lymphatic endothelial cells and accumulate in the skindraining lymph nodes

Abstract: Lymphatic vessels have received considerable attention in recent years as delivery route for immune modulatory therapies to the lymph nodes. Lymph node targeting of immunotherapies and vaccines has been shown to significantly enhance their therapeutic efficacy. Lymphatics transport functions materials from peripheral tissues to the lymph nodes, including small 10 – 250 nm therapeutic nanoparticles. While size required to enter lymphatic vessels, surface chemistry is more poorly studied. Here, we probed the eff… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…In addition to identifying optimum surface characteristics for lymphatic delivery, we also provided some of the first insight on the transport mechanisms involved in the transport of nanoparticles across lymphatic barriers. We found that both paracellular and transcellular transport mechanisms were key in crossing lymphatic barriers, with LECs relying on clathrinmediated endocytosis to mediate transport of PEGylated nanoparticles (McCright et al, 2020).…”
Section: Nanomaterial-based Lymphatic Targetingmentioning
confidence: 95%
See 1 more Smart Citation
“…In addition to identifying optimum surface characteristics for lymphatic delivery, we also provided some of the first insight on the transport mechanisms involved in the transport of nanoparticles across lymphatic barriers. We found that both paracellular and transcellular transport mechanisms were key in crossing lymphatic barriers, with LECs relying on clathrinmediated endocytosis to mediate transport of PEGylated nanoparticles (McCright et al, 2020).…”
Section: Nanomaterial-based Lymphatic Targetingmentioning
confidence: 95%
“…They found that the 30 nm formulations were transported into lymph nodes and taken up by CD8 + dendritic cells more effectively than 100 nm and 200 nm formulations of the solid lipid nanoparticles (Nakamura et al, 2020). Recent work by our group has also found that polyethylene glycol (PEG)-coated 40 nm nanoparticles were able to cross lymphatic barriers more efficiently than 100 nm PEG-coated nanoparticles (McCright et al, 2020).…”
Section: Nanomaterial-based Lymphatic Targetingmentioning
confidence: 99%